2014
DOI: 10.1007/s10266-014-0174-1
|View full text |Cite
|
Sign up to set email alerts
|

Immediate endodontic access cavity sealing: fundamentals of a new restorative technique

Abstract: Endodontic access cavity sealing is conventionally performed after endodontic irrigation, referred to as delayed endodontic sealing (DES). Evidence shows that endodontic irrigation with NaOCl decreases dentinal bond quality and could cause coronal leakage. Access cavity sealing before endodontic irrigation is a new restorative approach, referred to as immediate endodontic sealing (IES). The primary aim of this in vitro study was to investigate whether IES improved internal adaptation. The secondary aim was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“… 95 , 100 A variant of IDS undertaken in the access cavity of teeth subjected to endodontic treatment (immediate endodontic sealing) has been shown to reduce coronal leakage, which is the major cause of failure. 101 In a recent study, Ashy et al 8 identified a better marginal adaptation immediately after cementation and a better internal adaptation after thermocycling, when IDS was applied, compared with that using the conventional method (DDS). However, there was no significant difference in marginal adaptation after thermocycling among the two techniques examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 95 , 100 A variant of IDS undertaken in the access cavity of teeth subjected to endodontic treatment (immediate endodontic sealing) has been shown to reduce coronal leakage, which is the major cause of failure. 101 In a recent study, Ashy et al 8 identified a better marginal adaptation immediately after cementation and a better internal adaptation after thermocycling, when IDS was applied, compared with that using the conventional method (DDS). However, there was no significant difference in marginal adaptation after thermocycling among the two techniques examined.…”
Section: Resultsmentioning
confidence: 99%
“…Possible benefits mainly concern favorable μTBS values. De Rose et al 2015 101 In vitro Internal adaptation Evaluated the effect of immediate endodontic sealing (Clearfil SE Bond + Majesty Flow/Majesty Posterior) and the composite viscosity on internal adaptation of the final restoration. Immediate endodontic sealing significantly improved internal adaptation compared with that using delayed endodontic sealing, and composite viscosity did not affect internal adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…Wattanawongpitak et al performed an in vitro study investigating coronal root canal dentine showed a significantly inferior microtensile bond strength after etch‐and‐rinse adhesive or self‐etch adhesive application in specimens treated with EDTA followed by NaOCl (Wattanawongpitak et al, 2009). A study of de Rose et al assessing the internal adaptation of composite restorations placed in endodontic cavities by scanning electron microscopy indicated a decline of the adhesive bond to dentine and enamel due to contact with NaOCl (Rose et al, 2015). Since NaOCl is the most effective antibacterial root canal irrigant and essential in endodontic therapy, a sufficiently long NaOCl contact time was selected to allow NaOCl to penetrate the dentinal tubules, and EDTA was applied to remove the smear layer according to best clinical practice (Ayhan et al, 1999; Rossi‐Fedele & Rödig, 2022; Ruksakiet et al, 2020; Violich & Chandler, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Literature has reported improved internal adaptation of composite resin to dentin with IES than with DES. 6 IES can be done in conditions of non-vital teeth where irrigation with NaOCl for dissolution of pulpal tissue may not be required in the initial stages. Whereas in the case of vital teeth, there will be a need for the dissolution of pulpal tissue, which makes the use of NaOCl a must because of its tissue dissolving capacity.…”
Section: Introductionmentioning
confidence: 99%